Young People’s Experiences Using a Digital Mental Health Tool to Support Their Care in a Real-World Service: Lived Experience–Led Qualitative Study - Carla Gorban; Min K Chong; Adam Poulsen; Ashlee Turner; Haley M LaMonica; Sarah McKenna; Elizabeth M Scott; Ian B Hickie; Frank Iorfino (JMIR Mental Health)
Abstract BackgroundThe uptake of digital mental health tools (DMHTs) in mental health services is suboptimal, limiting key avenues to facilitate personalized and measurement-based care. This misses critical opportunities for enhanced patient-clinician communication, improved assessment, and early intervention. ObjectiveThis paper aims to understand young people’s experiences and perceptions of engaging with a DMHT to support their care in a real-world setting over time. MethodsThis study is part of a larger randomized controlled trial, where an added human support, the digital navigator (DN), provided technological and engagement assistance for young people to use a DMHT as part of usual care. The DN conducted 118 semistructured interviews with 73 young people (mean age 22.7, SD 2.7 y) at baseline and 3-, 6-, and 12-month follow-up visits. ResultsWe found that the majority of young people were enthusiastic about incorporating a DMHT into their care when they understood its potential to facilitate shared decision-making and enhance self-awareness of their mental health. Notably, the DN’s support was effective in fostering this understanding at the initial stages of implementation. However, it was evident that the lack of clinician buy-in for using the DMHT posed a risk of disillusionment to young people’s sustained engagement with the tool. Young people perceived that clinician uptake of the tool was poor, limiting its perceived value addition and sustainability. ConclusionsYoung people want to use DMHTs in their care and DNs can effectively facilitate implementation through ongoing engagement and technical support. However, successful implementation of DMHTs also depends on broader systemic factors, particularly on clinician and service engagement. Future research should examine how to address these contextual barriers and optimize DN support for implementation and sustained engagement of DMHTs.